2013
DOI: 10.1186/1743-7075-10-28
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of carnitine leads to an activation of the IGF-1/PI3K/Akt signalling pathway and down regulates the E3 ligase MuRF1 in skeletal muscle of rats

Abstract: BackgroundRecently, it has been shown that carnitine down-regulates genes involved in the ubiquitin-proteasome system (UPS) in muscle of pigs and rats. The mechanisms underlying this observation are yet unknown. Based on the previous finding that carnitine increases plasma IGF-1 concentration, we investigated the hypothesis that carnitine down-regulates genes of the UPS by modulation of the of the IGF-1/PI3K/Akt signalling pathway which is an important regulator of UPS activity in muscle.MethodsMale Sprague–Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 46 publications
6
47
2
1
Order By: Relevance
“…Some studies suggest that LC promoted osteoblast proliferation and differentiation in vitro (43,44), while other studies indicated that LC inhibited proliferation in VSMCs (45). In this study, we found that the 10 μM LC positively affected osteoblast proliferation, but the higher concentration of LC (100 μM) slightly decreased osteoblast proliferation compared with the control.…”
Section: Discussionmentioning
confidence: 40%
“…Some studies suggest that LC promoted osteoblast proliferation and differentiation in vitro (43,44), while other studies indicated that LC inhibited proliferation in VSMCs (45). In this study, we found that the 10 μM LC positively affected osteoblast proliferation, but the higher concentration of LC (100 μM) slightly decreased osteoblast proliferation compared with the control.…”
Section: Discussionmentioning
confidence: 40%
“…In mice that are fed a high‐fructose diet which is known as an acquired model of insulin resistance, the presence of L‐carnitine reduced protein oxidation in the lens, and the decreased anti‐oxidative enzymes were recovered, thus preserving mitochondrial function 30. Moreover, the presence of L‐carnitine increases Akt phosphorylation and accelerates myotube formation in C2C12 cells31 and in the muscle of rats 32. These pleiotropic effects of L‐carnitine, including anti‐oxidative and anti‐inflammatory activities and maintaining Akt signaling, could play an important role in the protection of mitochondrial function in CKD conditions, especially in cases of higher IS accumulation, such as uremia.…”
Section: Discussionmentioning
confidence: 99%
“…It is speculated that the rise of IGF-1 levels,though statistically not significant (Table 1) in the treated rats is attributed to L-carnitine supplementation since no change in insulin was observed. Studies have confirmed that carnitine supplementation causes an increase in IGf-1 levels in rats, pigs, chickens and humans 55 . Since IGf-1 also has hypoglycemic effects, the decrease in blood glucose levels of CR+CAR+HG could be related to the increase in plasma IGf-1.…”
Section: Enzyme Activities Plasma Protein and Musclementioning
confidence: 86%